Intraoperative Tension Pneumothorax in a Patient With Remote Trauma and Previous Tracheostomy - Ana Mavarez-Martinez MD; Suren Soghomonyan MD, PhD; Gurneet Sandhu MD; Demicha Rankin MD (SAGE Publishing, 2016)
Many trauma patients present with a combination of cranial and thoracic injury. Anesthesia for these patients carries the risk of intraoperative hemodynamic instability and respiratory complications during mechanical ventilation. Massive air leakage through a lacerated lung will result in inadequate ventilation and hypoxemia and, if left undiagnosed, may significantly compromise the hemodynamic function and create a life-threatening situation. Even though these complications are more characteristic for the early phase of trauma management, in some cases, such a scenario may develop even months after the initial trauma. We report a case of a 25-year-old patient with remote thoracic trauma, who developed an intraoperative tension pneumothorax and hemodynamic instability while undergoing an elective cranioplasty. The intraoperative patient assessment was made even more challenging by unexpected massive blood loss from the surgical site. Timely recognition and management of intraoperative pneumothorax along with adequate blood replacement stabilized the patient and helped avoid an unfavorable outcome. This case highlights the risks of intraoperative pneumothorax in trauma patients, which may develop even months after injury. A high index of suspicion and timely decompression can be life saving in this type of situation.